2021
DOI: 10.1002/app.51579
|View full text |Cite
|
Sign up to set email alerts
|

Amazon‐sustainable‐flour from açaí seeds added to starch films to develop biopolymers for active food packaging

Abstract: The wide consumption of açaí fruit results in large amounts of seeds which end up in waste. These seeds have an advantageous composition for the development of biopolymers due to their fibers content and active components (responsible by functional properties as antioxidant capacity). In the present work, active polymers were generated incorporating açaí seed flour in sustainable films produced using starch from broken rice grains as matrix. The effects of different seed flour content (0%, 5%, 10%, and 15%) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 58 publications
0
1
0
Order By: Relevance
“…Film preparation SPS/CMC from water hyacinth films was prepared through the cast casting technique, as previously described by Romani et al [25]. The SPS (3 % w/v) was homogenized in distilled water using a mechanical stirrer for 10 min at room temperature.…”
Section: Preparation Of Carboxymethyl Cellulose (Cmc) From Water Hyac...mentioning
confidence: 99%
See 1 more Smart Citation
“…Film preparation SPS/CMC from water hyacinth films was prepared through the cast casting technique, as previously described by Romani et al [25]. The SPS (3 % w/v) was homogenized in distilled water using a mechanical stirrer for 10 min at room temperature.…”
Section: Preparation Of Carboxymethyl Cellulose (Cmc) From Water Hyac...mentioning
confidence: 99%
“…The solubility in water (SW) of the films was adapted from the method by Romani et al [25] and Tongdeesoontorn et al [31]. Film samples were cut (2.0 cm 2 ) and dried in a hot air oven (Memmert, UN 110, Germany) at 105 ± 2 °C to establish their initial dry weight.…”
Section: Solubility In Water Moisture Content and Water Vapor Permeab...mentioning
confidence: 99%
“…A wide range of polyphenolic compounds can be found in the pulp extract of this fruit, but anthocyanins are the main components that enhance its antioxidant effect (Yamaguchi et al, 2015). In recent studies, products based on its extract (de Moura et al, 2012), seeds (Romani et al, 2022), and palm leaf (Gouveia Guedes et al, 2021), have shown that this plant can be used in several current technological processes. Some recent works have shown that the polysaccharide matrix of kefir grains is capable of forming antibacterial biofilms.…”
mentioning
confidence: 99%